Nucleases in gene-editing technologies: past and prologue - Li Dan-Yuan; Li Long-Qi; Liu Jun-Jie Gogo (National Science Open, 2023)
In recent decades, gene-editing technologies, typically based on deoxyribonucleases to specifically modify genomic sequences, have dramatically remodeled various aspects of life sciences, including fundamental research, breeding, and medical therapeutics. So far, four types of endonucleases have been adopted and optimized as gene-editing tools: meganuclease, ZFN, TALEN, and Cas nuclease from the CRISPR-Cas system. Each tool comes with its own advantages and limitations. Over the last ten years, RNA-guided Cas nucleases have been extensively investigated and successfully implemented in almost all mammalian cells due to their remarkable editing efficacy, high specificity, and flexibility in targeting the specific locus. Diverse Cas nuclease, together with meganuclease, ZFN, and TALEN, represent the key strategies for nuclease-based gene editing. However, systematic introductions and comparisons among four types of nucleases are not yet available. Here, we overview the capabilities of four types of nucleases along the development history of gene editing and describe the molecular mechanisms of substrate recognition and cleavage. Particularly, we summarize the promising CRISPR-Cas systems as well as modified tools applied for gene editing in the eukaryotic genome. Moreover, how the re-modulated nucleases and other nucleases, either naturally occurring or AI-designed, might manipulate DNA sequences is discussed and proposed.